Rate expectations: What can and cannot be done about rating agencies - Nicolas Véron (Bruegel, 2011)
Credit rating agencies have been under the spotlight since the beginning of the current financial crisis. They failed in their assessment of US residential mortgage- based securities in the mid-2000s. Nevertheless, investors generally consider credit ratings useful to help form their views on credit risks. The global market for credit ratings is very concentrated, ostensibly as a consequence of high natural barriers to entry. All three leading rating agencies have headquarter functions in the US, but there is no compelling evidence that this has created an analytical bias. Tighter regulation of rating agencies can be envisaged but is unlikely to have a material positive effect on ratings quality. Better standardised public disclosures on risk factors by issuers are the most promising avenue for future improvements in credit risk assessments.
Keywords: 330; Finanzmarktkrise; Kreditwürdigkeit; Kreditrisiko; Ratingagentur; USA